2022
DOI: 10.1002/open.202200169
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of (−)‐Isopulegol‐based 1,3‐Oxazine, 1,3‐Thiazine and 2,4‐Diaminopyrimidine Derivatives

Abstract: A series of novel heterocyclic structures, namely 1,3‐oxazines, 1,3‐thiazines and 2,4‐diaminopyrimidines, were designed and synthesised. The bioassay tests demonstrated that, among these analogues, 2,4‐diaminopyridine derivatives showed significant antiproliferative activity against different human cancer cell lines (A2780, SiHa, HeLa, MCF‐7 and MDA‐MB‐231). Pyrimidines substituted with N 2 ‐( p ‐trifluoromethyl)aniline, in particular, displayed a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…However, the utilised cancer panel detected no substantial cell line selective action. In addition, some compounds (11)(12)(13)(14) exhibited more pronounced antiproliferative activity than the reference agent cisplatin, and non-cancerous fibroblast cells were damaged in the same concentration range, indicating a general cytotoxic property of the tested substances.…”
Section: In Vitro Antiproliferative Studies Of Steviol-based Aminotri...mentioning
confidence: 95%
See 2 more Smart Citations
“…However, the utilised cancer panel detected no substantial cell line selective action. In addition, some compounds (11)(12)(13)(14) exhibited more pronounced antiproliferative activity than the reference agent cisplatin, and non-cancerous fibroblast cells were damaged in the same concentration range, indicating a general cytotoxic property of the tested substances.…”
Section: In Vitro Antiproliferative Studies Of Steviol-based Aminotri...mentioning
confidence: 95%
“…3.3.7. (4R,4aS,6aR,7R,8R,11aS,11bS)-Methyl 8-((((R)-1-(4-Fluorophenyl)ethyl)amino)methyl)-7,8,9-trihydroxy-4,11bdimethyltetradecahydro-6a,9-methanocyclohepta[a]naphthalene-4-carboxylate (11) The reaction was accomplished with (R)-4-fluoro-α-methylbenzylamine, as described in the general procedure. Yield: 68 mg (50%); white crystals; m.p.…”
Section: General Procedures For Preparation Of Aminotriols With Prima...mentioning
confidence: 99%
See 1 more Smart Citation
“…2,4-Diaminopyrimidine derivatives with potent antiproliferative activity were prepared starting from pinaneand (−)-isopulegol-based 1,3-aminoalcohols. 20,21 In our previous work, we designed and evaluated the antiproliferative activity of a series of N-substituted allo-gibberic acid-based aminodiols. We found that N-naphthylethyl-substituted aminodiol derivatives showed the most promising antiproliferative activity.…”
Section: Introductionmentioning
confidence: 99%
“…2,4-Diaminopyrimidine derivatives with potent antiproliferative activity were prepared starting from pinane- and (−)-isopulegol-based 1,3-aminoalcohols. 20,21…”
Section: Introductionmentioning
confidence: 99%